Silicon nitride / zinc composite negative electrode, preparation thereof and application of silicon nitride / zinc composite negative electrode in zinc battery

By using silicon nitride/zinc composite anode in aqueous zinc ion batteries, combined with rapid annealing treatment and joint control of viscous carbon sources, the problem of poor stability of zinc negative electrodes is solved, and the anti-corrosion and electrochemical performance of the battery is significantly improved.

CN119542336AActive Publication Date: 2025-02-28HUNAN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311111787.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28
Estimated Expiration
2043-08-31

AI Technical Summary

Technical Problem

The poor stability of the zinc negative electrode in aqueous zinc ion batteries leads to low efficiency and poor circulation stability, and the formation of zinc dendrites will lead to the risk of battery short circuit.

Method used

The silicon nitride/zinc composite negative electrode is adopted to form a silicon nitride film with a porous structure on the current collector, and the zinc metal source is combined on its porous structure and surface, combined with the combined control of a fast annealing treatment and a viscous carbon source to improve the corrosion resistance and electrochemical properties of the negative electrode.

Benefits of technology

It significantly improves the corrosion resistance and electrochemical properties of the zinc negative electrode, inhibits the growth of zinc dendrites, and enhances the cycle stability and Coulomb efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542336A_ABST
    Figure CN119542336A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of zinc battery materials, and particularly discloses a silicon nitride / zinc composite negative electrode which comprises a current collector, a silicon nitride film which is loaded on the surface of the current collector and has a porous structure, and a zinc metal source which is compounded on the porous structure and the surface of the silicon nitride film. The preparation method comprises the following steps: compounding a precursor layer containing silicon nitride and a viscous carbon source on the current collector, then rapidly heating to T at a rate of 50-300 DEG C / s, carrying out heat preservation, carrying out annealing treatment, and forming the porous silicon nitride film on the current collector to obtain the current collector-porous silicon nitride composite material. The invention also comprises application of the negative electrode. According to the method disclosed by the invention, the electrochemical performance of the prepared negative electrode can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to the technical field of aqueous zinc batteries. Background Art

[0002] Energy and environment are two major issues that must be addressed for human survival and social development today. With the depletion of fossil resources such as coal and oil and the deteriorating environment, the development of renewable energy such as solar energy, wind energy and hydropower has become a global trend. Long-life, highly safe and environmentally friendly energy storage devices are the key to the development of the above renewable energy. Batteries, as a highly efficient electrochemical energy storage device, have been widely used in electric vehicles and mobile communications. It is of great significance to develop a new green and environmentally friendly battery system with high specific energy.

[0003] One of the current research focuses is to develop a high-energy-density aqueous battery system. Aqueous zinc-ion batteries have high safety, and the chemical properties of the negative electrode zinc are relatively stable. The resources of zinc are also very abundant, and there is a suitable electrochemical window in near-neutral and weakly acidic electrolytes. Although the zinc negative electrode has many advantages, there are still many problems in practical use. Studies have shown that zinc is prone to form dendrites during deposition. The main problem affecting the application process of aqueous zinc batteries is the poor stability of the zinc negative electrode, which leads to low coulombic efficiency and poor cycle stability of zinc ion batteries. The formation of zinc dendrites originates from the deposition of zinc at the interface between the negative electrode and the electrolyte. Dendrite fracture will form "dead zinc", and severe dendrites have the risk of puncturing the diaphragm and causing the battery to short-circuit. The zinc dendrite problem restricts the application process of aqueous zinc-ion batteries. It can be seen that inhibiting the growth of zinc dendrites is of great significance to improving the performance of aqueous zinc-ion batteries. At the same time, hydrogen evolution corrosion of zinc metal will produce hydrogen, causing the sealed battery to bulge and destroy the sealed packaging structure; at the same time, OH will also be produced - , which reacts with zinc to form zinc oxide or other zincate byproducts, passivating the surface of metallic zinc, reducing the active area of ​​the electrode, increasing polarization, and destroying the cycle stability. Therefore, finding a way to protect the zinc negative electrode and reduce the generation of zinc dendrites at the zinc negative electrode is of great significance for negative electrode protection. Summary of the invention

[0004] In view of the problems of unsatisfactory corrosion resistance and electrochemical performance such as cycle stability of existing zinc negative electrodes, the first purpose of the present invention is to provide a silicon nitride / zinc composite negative electrode, aiming to provide a zinc negative electrode with excellent corrosion resistance and electrochemical performance.

[0005] The second object of the present invention is to provide a method for preparing the silicon nitride / zinc composite negative electrode, aiming to prepare a zinc negative electrode with excellent corrosion resistance and electrochemical performance.

[0006] The third object of the present invention is to provide application of the silicon nitride / zinc composite negative electrode in zinc batteries.

[0007] A fourth object of the present invention is to provide a zinc battery comprising the silicon nitride / zinc composite negative electrode.

[0008] A silicon nitride / zinc composite negative electrode comprises a current collector, a silicon nitride film with a porous structure loaded on the surface of the current collector, and a zinc metal source composited on the pore structure and surface of the silicon nitride film.

[0009] The present invention discloses a new silicon nitride / zinc composite negative electrode, wherein a silicon nitride film with a porous structure (also referred to as a silicon nitride film layer) is composited on the current collector, and a zinc metal source is composited on the pore structure and surface of the silicon nitride film. The present invention has found that the negative electrode, based on the combined control of composition and structure, can achieve synergy, and can make the negative electrode exhibit excellent anti-corrosion performance, and not only that, it can also exhibit excellent electrochemical performance.

[0010] In the present invention, the current collector may be any material having electrical conductivity, for example, it may be at least one of titanium foil, carbon paper, and stainless steel mesh;

[0011] In the present invention, the silicon nitride in the silicon nitride film is at least one of amorphous nano silicon nitride powder, α-crystalline silicon nitride powder or β-crystalline silicon nitride powder;

[0012] The thickness of the silicon nitride film can be adjusted as needed, for example, it can be 50 nm to 3 μm, and further can be 1.5 to 2.5 μm;

[0013] In the present invention, the pore size of the silicon nitride film is 10nm to 1μm;

[0014] The loading amount of the zinc metal source can be adjusted as needed, for example, it can be 2 to 10 mg / cm 2 ;

[0015] In the present invention, the thickness of the silicon nitride / zinc composite negative electrode is 1 to 30 μm.

[0016] The present invention also provides a method for preparing the zinc composite negative electrode material, comprising compounding a precursor layer containing silicon nitride and a sticky carbon source on a current collector, then rapidly heating to T at a rate of 50 to 300°C / s, and maintaining the temperature for annealing, forming the porous silicon nitride film on the current collector, and obtaining a current collector@porous silicon nitride composite material;

[0017] The viscous carbon source is at least one of polyvinylidene fluoride, polytetrafluoroethylene, sodium alginate, styrene-butadiene rubber, sodium carboxymethyl cellulose, hydroxyethyl cellulose, hydroxymethyl propyl cellulose, polyacrylic acid, and polyimide; T is the decomposition temperature of the viscous carbon source T 0 0.9 to 2.5 times;

[0018] Then, a metal zinc source is compounded onto the current collector@porous silicon nitride material to obtain the silicon nitride / zinc composite negative electrode.

[0019] In the present invention, in order to successfully prepare the zinc composite negative electrode material and improve its performance, it is necessary to overcome the problems of unsatisfactory bonding between the silicon nitride film and the current collector, easy detachment of the metal zinc source powder, and unsatisfactory electrochemical performance. In view of the difficulty of the negative electrode described in the present invention, the present invention innovatively forms a precursor layer containing silicon nitride and a sticky carbon source on the current collector in advance, and then performs a rapid annealing treatment, and further cooperates with the combined control of the rapid annealing rate and temperature, so that the corrosion resistance of the negative electrode can be improved. In addition, it is also conducive to constructing active sites and structures adapted to zinc ions, which helps to improve the electrochemical performance of the negative electrode.

[0020] The present invention also shows that the combined control of the type and content of the viscous carbon source can help to further improve the composite morphology of silicon nitride and the current collector, and help to further construct a zinc ion-compatible structure and active sites.

[0021] In the present invention, the viscous carbon source is at least one of polyvinylidene fluoride and polytetrafluoroethylene. The present invention shows that using F-containing polymer as a viscous carbon source helps to further synergistically improve the electrochemical performance of the prepared material.

[0022] Preferably, the weight ratio of silicon nitride to the sticky carbon source is 5 to 10:1, preferably 6 to 9.5:1, and more preferably 8.5 to 9.5:1; in the present invention, the preferred ratio is further combined with the annealing process of the present application to further synergistically improve the electrochemical properties of the prepared material.

[0023] In the present invention, the precursor layer can be prepared by conventional means, for example, it can be formed based on a slurrying and coating method, and a typical step is, for example, slurrying silicon nitride and a viscous carbon source with a solvent, and then coating and drying to form the precursor layer;

[0024] Preferably, the solvent is at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), water, and ethanol;

[0025] In the present invention, the coating method can be an extrusion coating composite film making method or a spin coating method.

[0026] In the present invention, the precursor layer is subjected to the rapid annealing treatment, and the heating rate and the annealing temperature are jointly controlled, which is beneficial to regulating the bonding interface between the porous silicon nitride and the current collector, and is beneficial to constructing active sites and structures adapted to zinc ions, which helps to improve the corrosion resistance and cycle performance of the material.

[0027] Preferably, the heating rate is 100 to 250°C / s;

[0028] In the present invention, the temperature T in the annealing stage is the decomposition temperature T of the viscous carbon source. 0 For example, in the present invention, the temperature in the annealing stage may be between 300 and 800°C, and may be between 550 and 650°C.

[0029] In the present invention, the atmosphere during the annealing process is a protective atmosphere, such as an inert gas (Ar), N 2 At least one of .

[0030] Preferably, the annealing treatment time is 1 min to 120 min, preferably 5 to 50 min.

[0031] In the present invention, the metal zinc source can be loaded in the current collector@porous silicon nitride based on known processes. For example, the metal zinc source can be compounded in the porous silicon nitride material in the current collector@porous silicon nitride material by at least one method selected from melting, electrodeposition, coating, and vacuum infiltration.

[0032] In the present invention, the steps of the vacuum infiltration method are, for example: slurrying the zinc metal source and the binder to form a zinc slurry, then transferring it to the porous silicon nitride material in the current collector@porous silicon nitride material by vacuum infiltration, and drying to obtain the current collector@porous silicon nitride material.

[0033] In the present invention, the binder is at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and sodium alginate (SA);

[0034] The solvent of the zinc slurry is at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), water and ethanol.

[0035] The invention also provides an application of the zinc composite negative electrode, which is used for preparing a battery.

[0036] Preferably, it is used to prepare zinc batteries, and more preferably, it is used to prepare at least one of zinc solid-state batteries, aqueous zinc-manganese batteries, and zinc-vanadium batteries.

[0037] The present invention also provides a zinc battery, the negative electrode of which is the zinc composite negative electrode described in the present invention.

[0038] In the present invention, the zinc battery, except for the negative electrode as described in the present invention, other structures and components can be conventional. For example, depending on the positive electrode and the electrolyte, the zinc battery can further be at least one of a zinc solid-state battery, an aqueous zinc-manganese battery, and a zinc-vanadium battery.

[0039] The beneficial effects of the present invention are:

[0040] The present invention discloses a novel silicon nitride / zinc composite negative electrode, which, based on the combination of composition and structure, can provide a uniform deposition stable point for zinc ions, is beneficial to inhibit zinc dendrites, improve the electrolyte infiltration effect, and help shorten the transmission distance of zinc ions, thereby helping to synergistically improve the electrochemical properties of the negative electrode, such as corrosion resistance, capacity, rate and cycle stability.

[0041] The present invention also innovatively provides a method for preparing the negative electrode, which preliminarily forms a precursor layer comprising silicon nitride and a sticky carbon source on the current collector, and then performs a rapid annealing treatment, and further cooperates with the combined control of the rapid annealing rate and temperature, thereby improving the corrosion resistance of the negative electrode. In addition, it is also beneficial to construct active sites and structures adapted to zinc ions, which helps to improve the electrochemical performance of the negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a schematic diagram of the cross-sectional structure of Ti@silicon nitride obtained in step 1-2 of Example 1;

[0043] Figure 2 Schematic diagram of the surface structure of the negative electrode sheet obtained in steps 1-3 of Example 1;

[0044] Figure 3 This is a Tafel curve test diagram of a symmetrical battery in Example 1;

[0045] Figure 4 This is a cycle test diagram of the vanadium pentoxide full battery assembled in step 4 of Example 1;

[0046] Figure 5 This is a CV test curve of the manganese dioxide full battery assembled in step 5 of Example 1;

[0047] Figure 6 This is a comparison diagram of the AC impedance test in step 6 of Example 1;

[0048] Figure 7 yes Figure 6 A partial enlarged view of the AC impedance curve; DETAILED DESCRIPTION

[0049] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments, but this is not intended to limit the present invention.

[0050] An exemplary negative electrode preparation method of the present invention includes the following steps:

[0051] Nano silicon nitride powder and sticky carbon source are evenly dispersed in the corresponding solvent, and a magnetic stirring method is used to obtain silicon nitride slurry; then the silicon nitride slurry is applied to the surface of the titanium foil by an extrusion coating composite film-making method to form a silicon nitride coating, and then rapid annealing is performed to obtain the prepared porous silicon nitride coating. After slicing with a slicer, a porous titanium nitride negative electrode sheet is obtained. Then, zinc powder and a binder are evenly dispersed in the corresponding solvent to obtain a zinc powder slurry, and the zinc powder slurry is transferred to the porous silicon nitride coating by vacuum infiltration, and dried to obtain a silicon nitride / zinc powder composite negative electrode sheet material. Using the spin coating method requires slicing first, and then subsequent operations after coating.

[0052] In one embodiment of the present invention, the nano silicon nitride powder is at least one of amorphous nano silicon nitride powder, α-crystalline silicon nitride powder or β-crystalline silicon nitride powder.

[0053] In one embodiment of the present invention, the silicon nitride coated electrode sheet is prepared by using one of an extrusion blade coating composite film forming method and a spin coating method.

[0054] In one embodiment of the present invention, the porous silicon nitride coating has a thickness of 50 nm to 3 μm, and can further be 1.5 to 2.5 μm; the pore size is 10 nm to 1 μm, and the thickness of the silicon nitride / zinc powder composite negative electrode is 5 to 30 μm.

[0055] In one embodiment of the present invention, the viscous carbon source includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and sodium alginate (SA). The solvent includes at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), water, and ethanol. More preferably, at least one of PVDF, NMP, and DMF is used.

[0056] In the present invention, there is no particular requirement for the amount of solvent used in the slurrying stage, as long as the active material and the binder are sufficiently mixed to form a coatable slurry.

[0057] In one embodiment of the present invention, the coating, the nano silicon nitride powder coated electrode sheet is prepared by one or more methods of extrusion coating composite film making method and spin coating method.

[0058] In one embodiment of the present invention, the rapid annealing is performed at a rate of 50 to 300°C / s, a temperature of 300 to 800°C, and a time of 1 to 120 minutes. The annealing atmosphere is Ar;

[0059] The following are typical cases:

[0060] Example 1

[0061] Step (1) Preparation of zinc ion battery negative electrode material based on silicon nitride coating

[0062] Step (1-1): Silicon nitride nanopowder (D50 is 100 nm) and a viscous carbon source (polyvinylidene fluoride binder) are mixed in a mass ratio of 9:1, fully ground, and evenly dispersed in an appropriate amount of N-methylpyrrolidone. After stirring for 12 hours using a stirrer, a silicon nitride slurry is obtained;

[0063] Step (1-2): Then, the silicon nitride slurry is coated on the cut titanium foil surface by extrusion coating composite film forming method, and the coater is controlled to ensure that the thickness of the silicon nitride coating is 2 μm. Then, it is transferred to a rapid annealing furnace and heated to 320°C (marked as T) at a heating rate of 100°C / s, and annealed for 5 minutes to obtain a porous silicon nitride skeleton layer.

[0064] Step (1-3): Mix zinc metal powder and polyvinylidene fluoride binder in a mass ratio of 9:1, grind them thoroughly, and evenly disperse them in an appropriate amount of N-methylpyrrolidone. Use a stirrer to stir for 12 hours to obtain a metal zinc powder slurry. The slurry is evenly covered on the surface of the porous silicon nitride skeleton layer. Use a vacuum drying oven to vacuum-impregnate the electrode sheet, and then dry it at 60°C for 10 hours to obtain a silicon nitride / zinc powder composite negative electrode sheet (also called Si 3 N 4 @Zn, the loading amount of zinc metal is 5mg / cm 2 ). Its cross-sectional structure diagram is as follows Figure 1 The schematic diagram of its surface structure is shown in Figure 2 shown.

[0065] (2) Symmetrical battery constant current charge and discharge performance test

[0066] First, assemble a symmetrical battery, use the prepared electrode material as the electrode, and select 2 mol / L ZnSO as the electrolyte. 4 , Whatman glass fiber separator assembled CR-2032 button cell. The battery was charged and discharged at constant current. At 100mA / g, constant current charging for 0.5h and constant current discharging for 0.5h were repeated in alternating cycles. The test results showed that the overpotential of the symmetrical battery was 50mV.

[0067] (3) Symmetrical battery corrosion resistance test

[0068] The Tafel curve was used to evaluate the corrosion resistance of the porous silicon nitride / zinc powder composite negative electrode. Figure 3 As shown, the curves of the first cycle and the second cycle almost overlap, and it can be seen that the modified negative electrode has extremely strong corrosion resistance, and the corrosion current is 0.1 mA.

[0069] (4) Full battery constant current charge and discharge performance test

[0070] Assemble V 2 O 5 Full Battery:

[0071] V 2 O 5 positive electrode:

[0072] V 2 O 5 The powder and the polyvinylidene fluoride binder were mixed in a mass ratio of 9:1 and fully ground, then uniformly dispersed in an appropriate amount of N-methylpyrrolidone and stirred for 12 hours using a stirrer to obtain V 2 O 5 The slurry was evenly coated on the positive electrode current collector, and then dried at 60 ° C for 10 hours to obtain V 2 O 5 positive electrode:

[0073] The electrolyte is 2 mol / L ZnSO 4 The CR-2032 button cell is assembled with the cut Whatman fiberglass separator. The specific assembly sequence from top to bottom is CR-2032 positive electrode shell - V 2 O 5 -Glass Fiber Diaphragm-Si 3 N 4 @Zn-spring gasket-CR-2032 type negative electrode shell. After assembly, use MSK-L10 battery sealing machine to seal, with the negative electrode shell on top and the positive electrode shell on the bottom.

[0074] The battery was charged and discharged at constant current to test the different performance of the battery under high and low current. The high current was charged at constant current for 1 hour at 1A / g and discharged at constant current for 1 hour. The low current was charged at constant current for 4 hours at 100mA / g and discharged at constant current for 4 hours. The first charge and discharge curve of some full battery cycles is shown in Figure 1. Figure 4 shown.

[0075] (5) Zn / MnO 2 Full battery CV performance test

[0076] MnO was prepared by 2 Prepare the positive electrode with the same process and parameters as the positive electrode (refer to step 4 for V 2 O 5 The only difference is that the positive electrode uses MnO 2 As active material), the full battery was tested by CV using an electrochemical workstation. The results are as follows Figure 5 As shown. It can be analyzed: MnO 2The positive electrode material has an oxidation peak and two reduction peaks. The potential of the oxidation peak is about 1.592~1.594V, and the potentials of the two reduction peaks are 1.22V and 1.377V respectively. In the second cycle, the height of the reduction peak tends to decay. The oxidation peak shows that Zn 2+ Deposited on the zinc anode, the two reduction peaks indicate that H + , Zn 2+ Embedding.

[0077] (6) Zn / MnO 2 Full battery EIS impedance performance test

[0078] The full battery was tested using an electrochemical workstation. The AC impedance comparison chart is as follows: Figure 6 shown. Figure 7 for Figure 6 The partial enlarged diagram of the AC impedance curve shows that the diameter of the semicircular arc in the medium frequency range is very small, and the charge transfer resistance is very low. Compared with the impedance of a pure zinc battery, it is similar to V 2 O 5 The impedance of the positive electrode is also smaller than that of the positive electrode. The electrode electrical activity is improved to a certain extent after modification, but the experimental results are not as good as those of V 2 O 5 Positive battery.

[0079] Example 2

[0080] Compared with Example 1, the only difference is that the viscous carbon source is replaced by a mixture of polyvinylidene fluoride and sodium alginate in a mass ratio of 1:1.

[0081] The performance test was carried out according to steps (2) and (4) of Example 1, and the results were:

[0082] The overpotential of the symmetrical cell is 136mV, and the positive electrode is V 2 O 5 The first discharge capacity is 218 mAh / g, and the discharge capacity after 100 cycles is 156 mAh / g.

[0083] Example 3

[0084] Compared with Example 1, the only difference is that the amount of the viscous carbon source is changed. The experimental groups are:

[0085] A: The weight ratio of viscous carbon source: silicon nitride is 6:1;

[0086] B: The weight ratio of viscous carbon source: silicon nitride is 8:1;

[0087] The performance test was carried out according to the methods (2) and (4) of Example 1, and the results were:

[0088] Group A: Symmetrical cell with an overpotential of 118 mV and a positive electrode of V 2 O 5 The first discharge capacity is 233 mAh / g, and the discharge capacity after 100 cycles is 176 mAh / g.

[0089] Group B: Symmetrical cell with an overpotential of 94 mV and a positive electrode of V 2 O 5 The first discharge capacity is 241 mAh / g, and the discharge capacity after 100 cycles is 195 mAh / g.

[0090] Example 4

[0091] Compared with Example 1, the only difference is that the viscous carbon source, the temperature and the rate of the rapid annealing stage are changed. The experimental groups are:

[0092] A: The viscous carbon source is sodium alginate, and the heating rate in the rapid annealing stage is 50°C / s, the annealing temperature is 600°C, and the time is 10 min;

[0093] B: The heating rate of the rapid annealing stage is 150℃ / s, the annealing temperature is 400℃, and the time is 50min;

[0094] The performance test was carried out according to the methods (2) and (4) of Example 1, and the results were:

[0095] Group A: Symmetrical cell with an overpotential of 88 mV and a positive electrode of V 2 O 5 The first discharge capacity is 198 mAh / g, and the discharge capacity after 100 cycles is 163 mAh / g.

[0096] Group B: Symmetrical cell with an overpotential of 67 mV and a positive electrode of V 2 O 5 The first discharge capacity is 237 mAh / g, and the discharge capacity after 100 cycles is 206 mAh / g.

[0097] Example 5

[0098] Compared with Example 1, the only difference is that the silicon nitride porous membrane is prepared by spin coating. The experimental groups are:

[0099] A: Spin coating process: 5000r / min spin coating for 1min, 10000r / min spin coating for 1min, repeat 5 times;

[0100] B: Spin coating process: 5000r / min spin coating for 1min, 10000r / min spin coating for 1min, repeated 10 times;

[0101] The performance test was carried out according to the methods (2) and (4) of Example 1, and the results were:

[0102] Group A: Symmetrical cell with an overpotential of 50 mV and a positive electrode of V 2 O 5 The first discharge capacity is 264 mAh / g, and the discharge capacity after 100 cycles is 189 mAh / g.

[0103] Group B: Symmetrical cell with an overpotential of 56 mV and a positive electrode of V 2 O 5 The first discharge capacity is 247 mAh / g, and the discharge capacity after 100 cycles is 214 mAh / g.

[0104] Comparative Example 1

[0105] Compared with Example 1, the only difference is that the rapid annealing treatment is not performed (only coating-drying to obtain the electrode sheet), and the different negative electrode preparation process is:

[0106] Silicon nitride nanopowder and polyvinylidene fluoride binder were mixed in a mass ratio of 9:1 and fully ground, then evenly dispersed in an appropriate amount of N-methylpyrrolidone, and stirred for 12 hours using a stirrer to obtain silicon nitride slurry;

[0107] Then, the silicon nitride slurry was coated on the surface of the titanium foil by extrusion coating composite film making method, and the coater was controlled to ensure that the thickness of the silicon nitride coating was 2μm. The coating was dried at 60°C for 10 hours to obtain the coated silicon nitride material. The zinc powder was slurried and stirred in the same way, and the slurry was evenly covered on the surface of the silicon nitride coating layer, and dried at 60°C for 10 hours. Finally, the negative electrode material of the zinc ion battery for comparison was obtained after slicing with a pole slicer.

[0108] The performance test was carried out according to the methods (2) and (4) of Example 1. The results were as follows: the overpotential of the symmetrical battery was 205 mV, and the positive electrode was V 2 O 5 The first discharge capacity is 168 mAh / g, and the discharge capacity after 100 cycles is 64 mAh / g.

[0109] Comparative Example 2

[0110] Compared with Example 1, the only difference is that polyvinyl alcohol is used as the viscous carbon source.

[0111] The performance test was carried out according to the methods (2) and (4) of Example 1. The results were as follows: the overpotential of the symmetrical battery was 165 mV, and the positive electrode was V 2 O 5 The first discharge capacity is 174 mAh / g, and the discharge capacity after 100 cycles is 73 mAh / g.

[0112] Comparative Example 3

[0113] Compared with Example 1, the only difference is that the heating rate of the annealing stage in step 1-2 is 10°C / s, and other operations and parameters are the same as Example 1.

[0114] The performance test was carried out according to the methods (2) and (4) of Example 1. The results were as follows: the overpotential of the symmetrical battery was 290 mV, and the positive electrode was V 2 O 5 The first discharge capacity is 156 mAh / g, and the discharge capacity after 100 cycles is 45 mAh / g.

[0115] Comparative Example 4

[0116] Compared with Example 1, the only difference is that the temperature of the annealing stage is: A: 900°C; B: 200°C;

[0117] The performance test was carried out according to the methods (2) and (4) of Example 1, and the results were:

[0118] A: The overpotential of a symmetrical cell is 180mV, and the positive electrode is V 2 O 5 The first discharge capacity is 176 mAh / g, and the discharge capacity after 100 cycles is 67 mAh / g.

[0119] B: The overpotential of the symmetrical cell is 201mV, and the positive electrode is V 2 O 5 The first discharge capacity is 178 mAh / g, and the discharge capacity after 100 cycles is 132 mAh / g.

[0120] Comparative Example 5

[0121] Compared with Example 1, the only difference is that boron nitride is used to replace the silicon nitride.

[0122] The performance test was carried out according to the methods (2) and (4) of Example 1. The results were as follows: the overpotential of the symmetrical battery was 50 mV, and the positive electrode was V 2 O 5 The first discharge capacity is 239 mAh / g, and the discharge capacity after 100 cycles is 67 mAh / g.

[0123] Thus, it can be seen that the rapid annealing process of the present invention, combined with the joint control of the binder components, can achieve synergy and further improve the electrochemical properties of the prepared material.

Claims

1. A silicon nitride / zinc composite negative electrode, characterized in that: The invention comprises a current collector, a silicon nitride film with a porous structure loaded on the surface of the current collector, and a zinc metal source compounded in the pore structure and surface of the silicon nitride film.

2. The silicon nitride / zinc composite negative electrode according to claim 1, characterized in that: The current collector is at least one of titanium foil, carbon paper and stainless steel mesh; Preferably, the silicon nitride in the silicon nitride film is at least one of amorphous nano silicon nitride powder, α-crystalline silicon nitride powder or β-crystalline silicon nitride powder; Preferably, the thickness of the silicon nitride film is 50 nm to 3 μm, preferably 1.5 to 2.5 μm; Preferably, the pore size of the silicon nitride film is 10 nm to 1 μm; Preferably, the loading amount of the zinc metal source is 2 to 10 mg / cm 2 ; Preferably, the thickness of the silicon nitride / zinc composite negative electrode is 1 to 30 μm.

3. A method for preparing the zinc composite negative electrode material according to any one of claims 1 to 2, characterized in that: A precursor layer comprising silicon nitride and a sticky carbon source is compounded on the current collector, and then the temperature is rapidly raised to T at a rate of 50 to 300° C. / s, and the temperature is maintained for annealing to form the porous silicon nitride film on the current collector to obtain a current collector@porous silicon nitride composite material; The viscous carbon source is at least one of polyvinylidene fluoride, polytetrafluoroethylene, sodium alginate, styrene-butadiene rubber, sodium carboxymethyl cellulose, hydroxyethyl cellulose, hydroxymethyl propyl cellulose, polyacrylic acid, and polyimide; the T is 0.9 to 2.5 times the decomposition temperature T0 of the viscous carbon source; Then, a metal zinc source is compounded onto the current collector@porous silicon nitride material to obtain the silicon nitride / zinc composite negative electrode.

4. The method for preparing the zinc composite negative electrode material according to claim 3, characterized in that: The viscous carbon source is at least one of polyvinylidene fluoride and polytetrafluoroethylene; Preferably, the weight ratio of silicon nitride to the viscous carbon source is 5 to 10:1, preferably 6 to 9.5:1, and more preferably 8.5 to 9.5:1; Preferably, the precursor layer is formed based on a slurrying and coating method, the steps of which are: slurrying silicon nitride and a viscous carbon source with a solvent, and then coating and drying to form the precursor layer; Preferably, the solvent is at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), water, and ethanol; Preferably, the coating method is an extrusion coating composite film making method or a spin coating method.

5. The method for preparing the zinc composite negative electrode material according to claim 3, characterized in that: The heating rate is 100~250℃ / s; Preferably, the temperature T in the annealing stage is 1 to 2 times the decomposition temperature T0 of the viscous carbon source; Preferably, the atmosphere during the annealing treatment stage is a protective atmosphere; Preferably, the annealing treatment time is 1 min to 120 min, preferably 5 to 50 min.

6. The method for preparing a zinc composite negative electrode material according to any one of claims 3 to 5, characterized in that: The zinc metal source can be compounded in the porous silicon nitride material in the current collector@porous silicon nitride material by at least one method selected from the group consisting of melting, electrodeposition, coating, and vacuum infiltration; Preferably, the vacuum infiltration method comprises the following steps: slurrying the zinc metal source and the binder to form a zinc slurry, and then transferring the zinc slurry to the porous silicon nitride material in the current collector@porous silicon nitride material by vacuum infiltration, and drying to obtain the current collector@porous silicon nitride material.

7. The method for preparing the zinc composite negative electrode material according to claim 6, characterized in that: The binder is at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and sodium alginate (SA); The solvent of the zinc slurry is at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), water and ethanol.

8. Use of the zinc composite negative electrode according to any one of claims 1 to 2 or the zinc composite negative electrode prepared by the preparation method according to any one of claims 3 to 7, characterized in that: Use it to prepare batteries; Preferably, it is used to prepare zinc batteries, and more preferably, it is used to prepare at least one of zinc solid-state batteries, aqueous zinc-manganese batteries, and zinc-vanadium batteries.

9. A zinc battery, characterized in that: The negative electrode is the zinc composite negative electrode described in any one of claims 1 to 2 or the zinc composite negative electrode prepared by the preparation method described in any one of claims 3 to 7.

10. The zinc battery according to claim 9, characterized in that: The zinc battery is at least one of a zinc solid-state battery, an aqueous zinc-manganese battery, and a zinc-vanadium battery.

Citation Information

Patent Citations

  • Modification method of zinc metal negative electrode as well as product and application thereof

    CN112838211A

  • Negative electrode for zinc battery and zinc battery

    JP2021185560A